Nigeria school feeding program: Baseline cooks’ survey instrument - Andam, Kwaw S.; Amare, Mulubrhan; Gelli, Aulo; Kosec, Katrina; Abay, Kibrom A.; Bamiwuye, Temilolu; Fasoranti, Adetunji; Idowu, Ifetayo (International Food Policy Research Institute, 2024)
Nigeria School Feeding Program - Cooks Questionnaire